The Structure and Microstructure of Rising-Tone Chorus With Frequencies Crossing at f ~ 0.5 fce - Chen, Rui; Tsurutani, Bruce T.; Gao, Xinliang; Lu, Quanming; Chen, Huayue; Lakhina, Gurbax S.; Hajra, Rajkumar (My University, 2022)
Intense, midnight-to-dawn sector, near-equatorial, chorus rising tones which cross frequencies of_0.5_ce have been analyzed to determine their structures and possible substructures. Upper ð ´ð ´band (ð ´ð ´ â‰¥ 0.5ð ‘“ð ‘“ce ) chorus and â€œð ´ð ´gapâ€ (ð ´ð ´ âˆ¼ 0.5ð ‘“ð ‘“ce ) chorus are examined in detail for the first time. It is found that upper band chorus and gap chorus are composed of the same structure as lower ð ´ð ´ band (ð ´ð ´ â‰¤ 0.5ð ‘“ð ‘“ce ) chorus: they are composed of short-duration subelements, which are monochromatið ´ð ´c with ð ´ð ´ â‰¤ 1% . These findings have strong implications for the chorus element generation mechanism. Following Kennel and Petschek (1966, https://doi.org/10.1029/JZ071i001p00001) the overall chorus riser is most likely generated by anisotð ´ð ´ropic (ð ´ð ´âŸ‚âˆ•ð ‘‡ð ‘‡â€– > 1) âˆ¼10â€“100 keV substorm-injected electrons. Assuming cyclotron resonance, the upper band chorus is generated by the low energy portion of the electron spectrum. The often-present gap at _0.5_ce is related to Landau/cyclotron damping. This however is not the end of the story. There is another type of two-frequency chorus (called Type 2) for which the lower band is not well connected to the upper band. A Type 2 chorus reported previously by Fu et al. (2014, https://doi.org/10.1002/2014JA020364) has also been studied in detail. Both the lower band and upper band are composed of subelements which are monochromatic. Such a similar fine structure for the different type of chorus may imply a similar generation mechanism, for which the difference between them is just the energy range of resonant energetic electrons. One mechanism discussed here, generation by phase bunched electrons, will be tested in the near future. Plain Language Summary Understanding chorus structure and microstructure is essential toward understanding the wave generation mechanisms and wave-particle interaction consequences. In this paper we show that upper ð ´ð ´band (ð ´ð ´ â‰¥ 0.5ð ‘“ð ‘“ce ) chorus and gap chð ´ð ´orus (ð ´ð ´ âˆ¼ 0.5ð ‘“ð ‘“ce ) are composed of substructures (subelements) which are monochromatið ´ð ´c with ð ´ð ´ â‰¤ 1% . These are the same features of lower ð ´ð ´band (ð ´ð ´ â‰¤ 0.5ð ‘“ð ‘“ce ) chorus. The Kennel-Petschek theory therefore needs to be enlarged such that phase-bunching of âˆ¼10â€“100 keV substorm injected anisotropic electrons occur, which then â€œlaseâ€ to yield the monochromatic wave subelements. Coherent and monochromatic chorus can explain the rapid burstiness of ionospheric microburst X-ray structures. There is another type of upper band chorus, called Type 2 upper band chorus, where the lower band chorus elements are not clearly connected to the upper band chorus. A Type 2 chorus reported previously by Fu et al. (2014, https://doi.org/10.1002/2014JA020364) has been examined in this paper. The apparently unrelated upper band has been found to be composed of subelements which are monochromatic in nature. Thus the different type of chorus may be excited by a similar generation mechanism, for which the difference between them is only the energy interval of the resonant energetic electrons.
Keywords: Type-1 upper band chorus; Type-2 upper band chorus; Gap chorus; Monochromatic subelements